Applying Peer Feedback To Enhance High School EFL Students' Writing Skills In State High School 1 Rejotangan Tulungagung - Muhammad Rizal Muhaimin; Titik Lina Widyaningsih (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Writing is the most challenging skill in English language learning. Researchers at SMKN 1 Rejotangan observed that most students struggled with writing in English. To address this, they implemented the peer feedback method to enhance students' writing skills. The study aimed to investigate the effectiveness of peer feedback in improving students’ writing abilities. Using a convergent mixed-method design, the research involved 31 students from class XI AKC 2. Instruments included pre-tests, post-tests for quantitative data, and interviews for qualitative data. Quantitative analysis was conducted using a t-test with SPSS 27, and qualitative data were analyzed thematically. Results showed significant improvement in students' writing skills after using peer feedback, as indicated by a significance value of 0.00 < 0.05. Interviews with five selected participants also revealed positive responses. Hence, the peer feedback method positively impacted the writing abilities of class XI AKC 2 students at SMKN 1 Rejotangan.